Bacteriocins: Classification, properties, production and mode of action. (I) - METAXOPOULOS (Ι. ΜΕΤΑΞΟΠΟΥΛΟΣ) J.; MATARAGAS (Μ. ΜΑΤΑΡΑΓΚΑΣ) M.; DROSINOS (E. X. ΔΡΟΣΙΝΟΣ) E. H. (Journal of the Hellenic Veterinary Medical Society, 2018)
Bacteriocins are antimicrobial compounds synthesized by ribosomes. In the last years a variety of bacteriocins, produced by lactic acid bacteria, has been identified and characterized. As a result of these studies is that new knowledge regarding the biosynthesis, structure, production and mode of action of these proteinaceous compounds has been gained. The present review attempts to refer some of the available data with reference to the bacteriocins, which are important for the understanding of the whole mechanism of the production of bacteriocins. Additionally, some features and recent biology and biochemistry findings concerning these substances will be reported, in order to provide a general overview of the production and action of the bacteriocins.